(3GdahR GdUZjQ aj GdMceIs - (3CMeO Hf eMeO Hf jYbhH perSncnhrjg, CHh Ydj,J (B421 (3g` s
(3ChdgG (B:s
(3hYdi CeQ GdCejQ GdeXaQ GdSjO Ydi GdeSGFd GdKdGKI GdJi JTJed Ydi GdYdhe cdgG s
(3BNQgG (B:s
(3ef cJGH GdahR GdCcHQ GdPi fSJCfa HeTjFI Gddg s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B168s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B_ (3EjQGf (B(46) s
Keywords: (3GdadSaI hGdefWbs